Development, validation and translation of cardiopulmonary resuscitation and automated external defibrillator training and placement bilingual questionnaire - Chew, Keng Sheng; Liaw, Siew Yee; Ahmad Zulkarnain, Ahmad Zahedi; Wong, Shirly Siew Ling; Nariman Singmamae @ Nariman, binti Hama Sanamay; Dev Nath, Kaushal; Chan, Hiang Chuan (BMC Research Notes, 2019)
Objectives